'Brown Bess' vs 'Miss Minie'. (3rd July 2018) - Ferguson, Jonathan
Abstract : Following the publication of the article 'Trusty Bess': the Definitive Origins and History of the term 'Brown Bess', the author was made aware of an intriguing illustration that perfectly captures the meaning of that famous nickname. This short note details this archival document and sheds light on both its place in the lore of 'Brown Bess' and its wide historical context in terms of the Victorian attitudes to military small arms development.